Influence of Dietary Fibre and Protein Fractions on the Trace Element Bioaccessibility of Turnip Tops (Brassica rapa) Growing under Mediterranean Conditions - Fernando Cámara-Martos (Foods, 2024)
The objective of this work was to study the influence of three dietary fibre fractions (pectin, gum arabic and cellulose) and three protein fractions (casein, lactalbumin and soy) on the trace element bioaccessibility (Fe, Mn, Ni, Se and Zn) of turnip tops (B. rapa subsp. Rapa) growing under Mediterranean conditions. Then, it aimed to promote the use of this vegetable not only for direct fresh consumption but also as a main ingredient in the development of food mixtures. The results showed that soluble fibre fractions, such as pectin and gum arabic, can enhance the bioaccessibility of trace elements, such as Fe, Mn, Se and Zn. This effect was not proved for cellulose (an insoluble fibre fraction), in which, at best, no bioaccessibility effect was observed. Regarding the protein fractions, with the exception of Se, caseins and lactalbumin had a neutral effect on improving the trace element bioaccessibility. This did not hold true for soy protein, in which a considerable improvement in the bioaccessibility of Fe, Mn, Se and Zn was determined.